The principal's role in supporting professional learning communities - Duling, Karen S. (Kansas State University, 2012)
Increasing student achievement is at the forefront of the school reform movement. Today’s educators are called upon to raise academic standards to the highest level in history with common core standards that align with international benchmarks. One of the most rapidly-growing improvement efforts in today’s schools is the development of professional learning communities (PLCs). Research shows a link between PLCs and increased student achievement. Additional information is needed about how school leaders have successfully supported sustainable PLCs within their schools. The purpose of this multi-site case study was to understand the types of principal behaviors as perceived by both teachers and principals that are most meaningful in the support of PLCs. The study also examined the intersection of the dimensions of learning-centered leadership and the critical attributes of PLCs. This study concluded that in professional learning communities, principals and teachers share a vision for learning and address the needs of all learners. The following leadership dimensions are perceived to be important in the support of professional learning communities: the principal’s knowledge and involvement in curriculum and instruction, the principal’s knowledge and involvement in the assessment program, and the principal’s influence on organizational culture. The study also revealed that when learning-centered leadership and professional learning communities intersect, shared leadership and collective learning are perceived to occur. Commonalities among the five cases in this study were affirmed, but each school site also had unique characteristics. In particular, one site emerged as an exemplar for strong teacher leadership.
Keywords: Professional learning communities; Leadership; Elementary principal; Educational leadership (0449); Elementary Education (0524)